Isolation and Identification of Non Fermenting Gram Negative Bacilli: A Prospective Study - Mahajan, Ruchita; Neeraj, .; Sarika, .; Mahajan, Bella (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
Pseudomonas aeruginosa, Acinetobacter baumanii, Burkholderia cepacia complex (BCC), and Stenotrophomonas maltophilia are among the Non-Fermenting Gram-Negative Bacilli (NFGNB) pathogens that have been linked to nosocomial infections. NFGNB were earlier considered to be commensals or contaminants. The goal of this study was to identify the various nonfermenters isolated from patients hospitalised to our hospital in Jammu, which is a tertiary care centre. The laboratory obtained 4585 clinical specimens, including 1234 urine, 742 pus, and 1864 blood cultures collected in a brain-heart infusion broth, 110 endotracheal catheter tips, 529 CSF samples, and 115 body fluids. These samples were cultured at 37°C for 18-24 hours on blood agar, chocolate agar, and Mac Conkey's agar. The clinical isolates were identified using established methods and conventional biochemical assays. Non-fermenting Gram-negative bacilli were identified from 572 of 4585 clinical specimens, yielding a 12.40 percent isolation rate. The most prevalent strain was Pseudomonas aeruginosa, which accounted for 312 (54.54 percent), followed by Acinetobacter baumanii 235 (41.08%), Stenotrophomonas maltophilia 15 (2.62%), and Burkholderia cepacia complex 10 (1.70 percent). Thirteen isolates (86.66 percent) were sensitive to Colistin, while four (26.60 percent) were responsive to Imipenem in our study. As a result, NFGNB are becoming major opportunistic diseases that are resistant to standard antimicrobials. As a result, early diagnosis and the implementation of empirical therapy based on the institute's local antibiogram data will minimise mortality and enhance patient management.